Systems thinking and complexity science–informed evaluation frameworks: Assessment of The Economics of Ecosystems and Biodiversity for Agriculture and Food. Issue 170 (1st September 2021) - Bustamante, María; Vidueira, Pablo; Baker, Lauren
Abstract: Despite the increasing literature, applications, and discussions over the last 15 years, there remain questions about how to bring systems thinking and complexity science (STCS) into evaluation in ways that meaningfully enhance its practice, use, and results. One pathway forward is bridging the gap between the large STCS body of knowledge and evaluation practice by synthesizing STCS insights into actionable frameworks to support the work and role of those engaged in evaluation activities. This chapter aims to contribute to this challenge through two main goals. First, the authors develop an actionable STCS framework comprising ten guiding principles, identified through a review of STCS literature to support evaluation practitioners, researchers, and commissioners to bring STCS into evaluation. Secondly—and to test this STCS principles‐based framework—this chapter assesses the extent to which TEEBAgriFood, an STCS‐informed food systems evaluation framework, advances STCS into evaluation. Results provide learnings and insights about the use of STCS in evaluation design and practice.